Sustainable performance evaluation of the banking industry based on CPT-TOPSIS: a case study of commercial banks in China - Chao, Lu (Frontiers in Sustainability, 2024)
The issue of sustainable development in financial institutions has become a primary concern for both the industry and investors. This study proposes a comprehensive decision-making method by integrating Cumulative Prospect Theory (CPT) with the traditional TOPSIS model for the sustainability assessment of commercial banks. Building on previous research, this study establishes a multi-criteria framework under the Global Reporting Initiative (GRI) that includes five major dimensions: economic, social, environmental, governance, and financial, along with 15 indicators. The study employs this model to conduct a comprehensive evaluation of five Chinese commercial banks. The results indicate that the Bank of China (BOC) ranked first in sustainability performance, particularly excelling in the environmental dimension compared to the second-ranked Industrial and Commercial Bank of China (ICBC), highlighting the importance of environmental indicators in the sustainability assessment of commercial banks. Empirical analysis shows that this model considers cognitive biases at the psychological level while accounting for uncertainties and risk preferences, offering significant advantages over the entropy-weighted TOPSIS model. The contribution of this paper lies in the pioneering introduction of Cumulative Prospect Theory into the study of sustainable development in Chinese commercial banks, combined with 15 related indicators under the GRI framework, providing new theoretical and practical insights for banking performance and sustainability research. This model effectively narrows the gap between the sustainability assessment practices of large Chinese commercial banks and international standards and holds promise as a useful tool for analyzing and improving sustainable development strategies in the banking sector.